Preparing peacekeepers: an analysis of the African Contingency Operations Training, and assistance program command and staff operational skills course - Karis, Daniel Gerald (Kansas State University, 2010)
The United States (U.S.) response to events in Africa in the 1990s—warlords in Somalia, the genocide in Rwanda, the crisis in Burundi, and the destruction of the U.S. embassies in Kenya and Tanzania—was the development of the African Crisis Response Initiative (ACRI) followed by the African Contingency Operations Training and Assistance (ACOTA) program. This study examined the impact of the command and staff operational skills portion of the ACOTA program to determine how well it prepared Ghanaian commanders and staff officers to conduct peace support operations under the auspices of a legitimate mandate. The importance of this program was revealed in its wide acceptance by the African leaders of 24 participating nations, by its ongoing support by the U.S. State Department, and by the budgetary increases it has received from the U.S. Congress over the years. This case study used qualitative methods to capture and analyze the self-reported perceptions of the course participants. Findings discovered that the students perceived the program as effective; team building was a perceived strength; U.S.-Ghanaian cultural differences were not perceived as effecting training; the teaching methodology instilled confidence to perform the mission; and course reference material, books, and CD-ROMs were valued. Results also showed that the time allowed for the course was insufficient; contingency training did not familiarize students with their mission area; students required timely notification to attend the course in order to properly prepare; and the course benefited the junior officers more than the senior officers.
Keywords: Peace support operations; African studies; Ghana Armed Forces; African Contingency Operations Training Assistance Program; Military training; Adult education; Education, Adult and Continuing (0516)